Peran Media Sosial dalam Peningkatan Motivasi Belajar Pendidikan Agama Islam - M. Fani Burhan Firmansyah; Ardila Tiwi Puspita Sari; Nazala Syifaus Shudur; Aang Kunapei (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2024)
This research discusses the role of social media in increasing motivation to learn Islamic religious education. This research aims to examine the role of social media in increasing motivation to learn Islamic Religious Education among students. This research uses qualitative methods with literature studies. The research results show that social media has a significant influence in increasing motivation to learn Islamic Religious Education. Through platforms such as Facebook, Instagram, and YouTube, students have easy access to various educational content, discussions, and communities that strengthen their understanding and interest in Islamic Religious Education material. Apart from that, social media also provides opportunities for teachers to deliver material creatively and interactively, facilitating more interesting and inspiring learning. However, there are challenges such as the risk of invalid information and excessive use of social media. Therefore, a wise approach is needed in using social media to increase motivation to learn Islamic Religious Education, by strengthening education about social media criticism. It is hoped that this research can provide useful insights for the development of effective educational strategies in the context of using social media to increase learning motivation for Islamic Religious Education.